Unveiling magic from the middle ages: tomographic reading of a folded lead amulet from Dřevíč fortress (Czech Republic) - Vavřík, Daniel; Knauber, Konrad; Urbanová, Daniela; Kumpová, Ivana; Blažková, Kateřina; Šámal, Zdeněk (Archaeological and anthropological sciences, 2020)
The discovery of a singular magical leaden artefact from the Middle Ages in Central Bohemia provoked the ambition to visualize and decipher the text hidden inside while still keeping the object in its original folded state. To fulfil this goal, several X-ray tomographic scans were done in conjunction with advanced data processing. Though parts of the text still remain inaccessible or unclear, the Dřevíč amulet is the first medieval object of its kind ever to have been successfully virtually unfolded and read. Leaden amulets are still very rare and under-researched finds in the archaeological record, with just over a hundred surviving examples mainly found in Southern Scandinavia and Central Germany. They are testimonies to the once widespread practice of Christian curative magic with roots in older pagan traditions. Comparable charms and blessings are extant in countless medieval manuscripts, while similar amulets written on parchment and most other organic materials have not survived. The information gained through digital imaging revealed not only the amulet bearer’s name but also a number of yet unknown and personalized magic formulae destined to protect the bearer of the artefact unattested elsewhere.
Gesehen am 30.03.2020